The mediating effect of JIT on the relationship between SCOR Model and supply chain performance - Kamarudin, Nurhayati; Nizam, Nurul Zarirah (Academia Industry Networks, 2022)
The SCOR Model is one of the most applied reference models to support the description of supply chains and understanding the relationship between supply chain operation reference and supply chain performance. The SCOR model owes a standard thought to perceive an activity of the Supply Chain Council provides a framework for characterizing supply chain management practices and processes with better performance. Most manufacturing industry is aware of the importance of SCOR Model by implementing actual participation still not embraced (Ibrahim, A. U., Daniel, C. O., 2019). This study examines potentials for future extensions of the model. By analysis of 158 samples for this study. This study investigates the level of SCOR Model practices in Supply Chain performance and investigates the relationship between SCOR Model effect by mediating of Just-In-Time (JIT) and supply chain performance in Malaysia manufacturing industry based on the five decision areas provided in SCOR Model Version 10.0 (PLAN, SOURCE, MAKE, DELIVER, RETURN) and five key supply chain performance derived from supply chain business management. The questionnaire tool by SCC is used to analyse requirements on modelling tools to support the application of a respective extended SCOR Model. The results showed that planning processes are important in all SCOR supply chain planning decision areas. Collaboration was found to be most important in the Plan, Source and Make planning decision areas, while teaming was most important in supporting the Plan and Source planning decision areas. Process measures, process credibility and process integration were found to be most critical in supporting the deliver planning on the decision area. Based on the result of the regression models it can be concluded that SCOR Model to some extend contributes significantly and positively towards firm SC performance and various components of performance measurements. Using these results, the study discusses the implications of the ﬁndings and suggests several venues for future research that contribute for the new version of SCOR Model and for the future reference on improve performance in industry and society.